Statistics on Lithuanian Libraries: A Quantitative Analysis of Activities Implemented in 2022 (Relevant Tomorrow / Aktualu rytoj, 2022)
Statistics on library activities are perhaps the best indicators of the benefits of the libraries to society. On the other hand, those indicators also serve as the best criteria of the impact of decisions taken by public authorities (e.g., reorganization or liquidation of institutions) regarding library services: the formation of holdings, services tailored to readers and staff members, improvement of working conditions, etc. The article reviews and compares statistical indicators of 2022 and previous years related to the entire Lithuanian library network, the distribution of holdings, the number of registered readers, visits to libraries and the number of publications issued, the readership, and the number of workplaces available for readers and staff members. The analysis has showed that in 2022, as in previous years, the number of libraries has been decreasing, which, in turn, has an impact on public access to library services. In the aftermath of the pandemic, the number of physical visits to the libraries has doubled (compared to 2021), whereas the number of virtual visits has decreased. The Martynas Mažvydas National Library of Lithuania has contributed significantly to the increase in physical visits, accounting for almost 30% of the total number of visitors in the cultural sector in Lithuania.
Keywords: Lithuanian libraries; library activity; statistical indicators; quantitative analysis